Degradation of sulfamethoxazole in aqueous solution by dielectric barrier discharge plasma combined with Bi2WO6 -rMoS2 nanocomposite: Mechanism and degradation pathway. (May 2019) - Zheng, Ke; Sun, Yabing; Gong, Shi; Jiang, Guilin; Zheng, Xuesong; Yu, Zhongqing
Abstract: The feasibility of pollutant removal in aqueous solution by dielectric barrier discharge plasma in combination with Bi2 WO6 -rMoS2 composite photocatalyst was investigated by choosing sulfamethoxazole (SMZ) as the model pollutant. In this study, Bi2 WO6 -rMoS2 catalysts were synthesized by a modified hydrothermal method and characterized by TEM, XRD, XPS. The results showed that the Bi2 WO6 was well loaded on the surface of MoS2 . The influences of the main operating parameters including discharge voltage, initial concentration, initial pH, mass ratios and dosages of Bi2 WO6 -rMoS2 on the removal efficiency of SMZ were studied. The results revealed that the initial concentration of 20 mg L −1 SMZ solution (100 mL) could be degraded by 97.6% with the addition of 0.08 g L −1 Bi2 WO6 -rMoS2 (1 wt%) at 9 kV after 21 min, compared with 72.5% by single dielectric barrier discharge plasma. Even after four cycling runs, Bi2 WO6 -rMoS2 (1 wt%) still remained high removal efficiency of SMZ. Moreover, the yields of hydrogen peroxide (H2 O2 ) and Ozone (O3 ) in plasma discharge process were also investigated, and the results exhibited that adding Bi2 WO6 -rMoS2 could notably influence the amount of O3 and H2 O2 . Finally, ten intermediates of SMZ degradation were identified, and the proposed SMZ degradation pathways were deduced based on the detected intermediates. Highlights: Bi2 WO6 -rMoS2 nanocomposite was first applied with dielectric barrier discharge (DBD) plasma. The Bi2 WO6 -rMoS2 showed efficient synergistic effect with DBD plasma for various processing parameters. The property changes of Bi2 WO6 -rMoS2 nanocomposite after plasma treatment were characterized. The mechanism and possible pathways of SMZ degradation in plasma/Bi2 WO6 -rMoS2 system were proposed.